Krisis Harapan Generasi Muda Dalam Fenomena #Kaburajadulu Di Tiktok: Studi Komunikasi Digital - Yusran, Yusran (Universitas Brawijaya, 2025)
This study examines the phenomenon of the hashtag #KaburAjaDulu on TikTok as a form of digital expression through which Indonesian youth articulate collective disillusionment toward domestic employment conditions and future socioeconomic prospects. Departing from prior studies that approach youth unemployment and migration from economic or policy perspectives, this research positions #KaburAjaDulu as a communicative and discursive practice embedded within digital media dynamics. Employing a descriptive qualitative design with a netnographic approach, this study analyzes 50 TikTok videos tagged with #KaburAjaDulu, collected between June and August 2025. Data were obtained through observation complemented by digital sentiment analysis using Brand24. The analytical framework integrates framing analysis and symbolic representation within digital content. The findings reveal that #KaburAjaDulu functions not merely as an expression of individual aspiration to work abroad, but as a collective discursive framing of crisis, reflecting structural dissatisfaction with the national labor system. The dominant negative sentiment and recurrent narrative patterns portray domestic employment as stagnant and precarious, while foreign labor markets are idealized as rational and attainable alternatives. This study contributes to digital communication scholarship by demonstrating how TikTok operates as a discursive arena for the construction of collective identity, critique, and hope among digitally native youth.